The Contribution of Subsidies on the Welfare of Fishing Communities in Malaysia - Ali, Jamal; Abdullah, Hussin; Noor, Mohd Saifoul Zamzuri; Viswanathan, K. Kuperan; Islam, Gazi Nurul (International Journal of Economics and Financial Issues, 2017)
Subsidies can reduce the cost of fishing operations and enhance revenues that make fishing enterprises more profitable. However, in Malaysia, overcapitalization and excessive fishing capacity leading to the overexploitation of fishery resources. The study obtained information about the type of fishing subsidies that has been given to fishing communities, benefits earned from these subsidies and views on the best possible policy directions for fisheries subsidy that will redirect funds towards promoting sustainable livelihoods and food security. Data collected for the study from three fishing districts of Peninsular Malaysia (Kedah, Perak, and Terengganu) through face to face interview. A total 246 fisher respondents were selected through a random selection process from the list of fishers with the Department of Fisheries. This study used Institutional Analysis and Development (IAD) model, which is explaining the importance of community factor characteristics (attributes of community) such as fishing communities. The results also showed that subsistence allowance is less effective for the livelihoods of fisher because it makes fisherman more dependent on subsidy. The termination of this allowance will not affect fishermen’s livelihoods. However, both A and B boat participants put importance on this monthly allowance as they found it very useful during the crisis time. The results demonstrated that fuel subsidy was the most important item for the fisher as it reduced fishing operation costs. The fuel subsidy has important implication for fisheries resource sustainability. Most fisherman families depend solely on fishing for their livelihood. The government should undertake effective fisheries management to reduce fishing pressure in the sea. Keywords: Subsidies, Fisheries resources, Marine Resources, Malaysia JEL Classifications: Q22, O123, P35